Dough Rheology and Baked Product Texture 1990
DOI: 10.1007/978-1-4613-0861-4_2
|View full text |Cite
|
Sign up to set email alerts
|

The Viscoelastic Properties of Wheat Flour Doughs

Abstract: It should be evident that cereal scientists need to be able to measure and understand the fundamental mechanical properties of wheat flour doughs. Restated more precisely, the goal is to understand the relationships between the forces acting on dough, its subsequent deformation, and time. This goal has been the impetus for a great deal of research over the past 60 years. Several recent reviews (Hlynka, 1970;Hibberd and Parker, 1975b;Baird, 1983;Faubion et al. 1985; Faubion and Faridi, 1986) present the rationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
53
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 29 publications
1
53
0
Order By: Relevance
“…A similar trend was also observed for the dough characteristics of mixtures of wheat flour with different protein contents and sago starch (Zaidul et al, 2004). Faubion and Hoseney (1989) reported that the water-binding capacity of starch granules has been postulated to have a strong effect on dough rheology. It is evident that the adsorption depends not only on the types of protein but also on the percent of starch.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…A similar trend was also observed for the dough characteristics of mixtures of wheat flour with different protein contents and sago starch (Zaidul et al, 2004). Faubion and Hoseney (1989) reported that the water-binding capacity of starch granules has been postulated to have a strong effect on dough rheology. It is evident that the adsorption depends not only on the types of protein but also on the percent of starch.…”
Section: Resultssupporting
confidence: 76%
“…It is evident that the adsorption depends not only on the types of protein but also on the percent of starch. However, higher absorption indicates that more water is required to reach a desired consistency in a commercial process, but does not indicate the exact amount (Faubion and Hoseney, 1989). In addition to water absorption, the shape of the farinogram is characterised by the flour.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wheat dough is classified as viscoelastic material (Faubion & Hoseney, 1990) which has elastic and viscous characteristics conferred by gluten. Gluten network is formed by hydrophobic interactions between water and protein polymers of the flour (mainly glutenins and gliadins).…”
Section: Introductionmentioning
confidence: 99%
“…Rheology of wheat dough is broad, and the tests utilized are diverse. Initially, empirical tests were more used than the fundamental tests, but disadvantages were seen such as: dependence on the instrument, the form and quantity of the sample utilized and lack of theoretical basis (Faubion & Hoseney, 1990), which led to the development of fundamental tests. The most important fundamental viscoelastic tests utilized for wheat dough are the force-deformation ratio, creep test, the dynamic test and stress-relaxation test (Mohsenin, 1978).…”
Section: Introductionmentioning
confidence: 99%